2013
DOI: 10.1002/clen.201200109
|View full text |Cite
|
Sign up to set email alerts
|

Copper Biosorption by Spent Coffee Ground: Equilibrium, Kinetics, and Mechanism

Abstract: The potential use of spent coffee ground (SCG) for the removal of copper has been investigated as a low‐cost adsorbent for the biosorption of heavy metals. Adsorption batch experiments were conducted to determine isotherms and kinetics. The biosorption equilibrium data were found to fit well the Freundlich model and an experimental maximum biosorption capacity of copper ions 0.214 mmol/g was achieved. The biosorption kinetics of SCG was studied at different adsorbate concentrations (0.1–1.0 mM) and stirring sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 53 publications
2
35
0
2
Order By: Relevance
“…Based on these changes we could infer that the main ligand atoms that interacted with Cu(II) ions were O, N, and S. Therefore, hydroxyl, amino, carboxyl, carbonyl, and sulfhydryl groups present on the HPIBY biomass surface were responsible for Cu(II) ions biosorption. The importance of hydroxyl, amino, carboxyl, and carbonyl groups was also noticed in copper adsorption from aqueous solutions by diverse biosorbents, such as: chemically pretreated S. cerevisiae, Posidonia oceanica, peat, spent coffee ground, and rubber leaf powder [10,[45][46][47]. In addition, we found that sulfhydryl groups from cysteine rich peptides were involved in Cu(II) ions adsorption.…”
Section: Ftir Spectroscopy Analysismentioning
confidence: 58%
“…Based on these changes we could infer that the main ligand atoms that interacted with Cu(II) ions were O, N, and S. Therefore, hydroxyl, amino, carboxyl, carbonyl, and sulfhydryl groups present on the HPIBY biomass surface were responsible for Cu(II) ions biosorption. The importance of hydroxyl, amino, carboxyl, and carbonyl groups was also noticed in copper adsorption from aqueous solutions by diverse biosorbents, such as: chemically pretreated S. cerevisiae, Posidonia oceanica, peat, spent coffee ground, and rubber leaf powder [10,[45][46][47]. In addition, we found that sulfhydryl groups from cysteine rich peptides were involved in Cu(II) ions adsorption.…”
Section: Ftir Spectroscopy Analysismentioning
confidence: 58%
“…Therefore, the SCGs were pretreated with 0.1 M NaOH (Fisher Chemical, Fair Lawn, NJ, USA) to remove the soluble materials as described in Dávila-Guzmán, N.E. et al [19]. The SCGs were washed repeatedly with deionized water after the pre-treatment with NaOH until a value of pH close to 6 was achieved.…”
Section: Spent Coffee Grounds (Scgs)mentioning
confidence: 99%
“…Then, it would be very interesting to find out an application to reuse other precursors of activated carbon production especially from agricultural wastes, which are inexpensive, abundantly available, and renewable materials. From the literature, date bead , spent Coffee Ground , rice husks , almond shells , and sawdust were used to prepare activated carbons. Olive stone (OS) waste residue as a raw material for the production of activated carbon can be considered as one of the best candidate among the agricultural wastes because it is cheap and quite abundant, especially in Mediterranean countries; however, its utilization has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%